Kekuatan Pembuktian Akta Notaris dalam Sengketa Waris Hak atas Tanah antara Hukum Adat dan Hukum Perdata di Indonesia - Muthmainnah (AHKAM, 2026)
The dualism between state law and customary law creates juridical complexities in the transfer of rights to customary communal land and family inheritance in Indonesia, particularly when notaries must ensure formal legal certainty through authentic deeds while simultaneously protecting the communal values of customary law communities. This study aims to analyze the synchronization of provisions in the Indonesian Civil Code, the Notary Office Law, and customary law, as well as to examine the evidentiary force of notarial deeds and the mechanisms for resolving inheritance disputes through judicial institutions. This study employed a normative juridical method using statutory, conceptual, and case approaches. The results indicate that although authentic deeds possess perfect evidentiary force, their legal standing may be set aside by a panel of judges if they are proven to disregard customary communal rights or contain substantive legal defects. These findings affirm the need for progressive legal interpretation and regulatory harmonization based on legal pluralism to balance formal legal certainty with substantive justice for the parties. Synergy between state law and local wisdom constitutes an essential foundation for strengthening legal protection and preventing land and inheritance disputes in the future.